Whole genome sequence data of an Antarctic bacterium, Arthrobacter sp. ES1 from the Schirmacher Oasis, East Antarctica - Teoh, Chui Peng; Yusof, Nur Athirah; Budiman, Cahyo; Cheah, Yoke Kqueen; Wong, Clemente Michael Vui Ling (Elsevier, 2023)
Arthrobacter is a coryneform bacterium in the family of Micrococcaceae. Arthrobacter species isolated from hostile environments are capable of producing interesting bioactive compounds, some of which may be a new class of antibiotics. Here, we present the complete genome sequence of Arthrobacter sp. ES1 isolated from Schirmacher Oasis in East Antarctica. Genomic DNA sequencing was performed using the Illumina MiSeq sequencer. Arthrobacter sp. ES1 has a genome size of 3,964,927 bp and a GC content of 65.73. The raw genome sequences have been deposited in the NCBI Sequence Read Archive database under the accession number, SRR20664316.